Perancangan Kontrol Optimal pada Model Matematika Bioekonomik - G.K. Gandhiadi (Jurnal Matematika, 2014)
This paper shows the initial research about the design of optimal investment policy of the public company in resource conservation, by using optimal control model. The mathematical bioeconomics model in using of mathematical modeling for resource conservation is a dynamics problem. The successfull of resource conservation management must fully take account of the time dimension for sustained equilibrium bioeconomics.  The design of a dynamic optimization model is solved  by optimal control strategy via maximum principle Pontryagin of Hamiltonian expressi. We have the conclusion that the optimization of present value for resource conservation very dependent of time domain, how long stock optimal can be sustained  for is given initial stock.